PELATIHAN PENINGKATAN PRODUKTIVITAS DAN PEMASARAN TELUR MENGGUNAKAN SISTEM PEMANTAUAN CERDAS - Rahsel, Yoeyong; Sari, Dita Novita; Saputra, Kurniawan; Pratomo, Panji Andhika (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role as the main pillar of the Indonesian economy, considering their significant contribution in supporting national economic stability and their ability to absorb most of the workforce in the country. Currently, Kurnia Jaya Farm, an MSME that focuses on chicken farming, faces various challenges such as low production capacity, management, marketing and inadequate cultivation skills. The purpose of PKM is to improve the ability of partners in the productivity of laying hens and market products well. The method used involves a series of systematic stages, including socialization activities, training, technology implementation, and providing ongoing assistance. The application of smart farming technology in livestock farming that allows automatic control and monitoring of livestock using sensors and machines, thereby increasing the effectiveness of livestock activities. While the business platform, to form a digital marketing ecosystem in increasing the marketing of livestock products. The results of this activity increase the knowledge and ability of partners in using smart farming and business platforms so as to minimize the obstacles faced by farmers and improve marketing.